Determinan Kualitas Laporan Keuangan (Studi pada Badan Usaha Milik Desa di Kecamatan Kubutambahan): (Studi pada Badan Usaha Milik Desa di Kecamatan Kubutambahan) - Febriyanti, Ni Luh Meilina; Devi, Sunitha; Wiguna, I Gd Nandra Hary (Vokasi : Jurnal Riset Akuntansi, 2025)
This study explores the influence of accounting understanding, use of accounting information systems, and internal control on the quality of BUMDes' financial reports in the Kubutambahan District. The population in this study was all BUMDes recorded in the Kubutambahan District, with data obtained from as many as 13 BUMDes. The sampling method used a saturated sample technique, so that a sample of 13 BUMDes was obtained, with the research respondents being the chairman, secretary, treasurer, and supervisor of BUMDes in Kubutambahan District, a total of 52 people. This study uses quantitative data types with primary data sources. Data was collected by distributing questionnaires to the chairman, secretary, treasurer, and supervisor of BUMDes in the Kubutambahan District. Data processing was done with the assistance of the IBM SPSS 26.0 program. The results of the study showed that partially and simultaneously accounting understanding, use of AIS, and internal control positively affected the quality of financial reports.